Pengembangan Media Pembelajaran Animasi Berbasis Canva pada Mata Pelajaran IPA Materi Bentuk Tubuh Hewan dan Fungsinya - Muhammad Rizqi Azqiyya; Nedin Badruzzaman; Dendy Saeful Zen M. F. (Medan Resource Center, 2023)
This study aims to determine the development of Canva-Based Animation Learning Media on the material form and function of animal bodies in class IV SDN Cilebut 01, and to determine the feasibility of learning process animation video products. The method used in this research is using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). In this study, validation tests were carried out on experts in the media and material fields to develop and perfect Canva-based animated video products for students. The results of the data from the validation of media experts were 98.2%, which means it was very feasible to implement and the results from material experts were 84% which were stated to be very feasible to implement. And based on a limited trial conducted on class IV students as many as 25 students obtained a proper score of 87.44%, which means that Canva-based animation video products are suitable for use in the learning process.